2018
DOI: 10.3390/w10040479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variations in Long-Duration Rainfall Intensity on Unsaturated Slope Stability

Abstract: In recent years, many scientific methods have been used to prove that the Earth's climate is changing. Climate change can affect rainfall patterns, which can in turn affect slope safety. Therefore, this study analyzed the effects of climate change on rainfall patterns from the perspective of rainfall intensity. This analysis was combined with numerical model analysis to examine the rainfall patterns of the Zengwen reservoir catchment area and its effects on slope stability. In this study, the Mann-Kendall test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The mechanism through which root-reinforced soil is related to concrete reinforcement mainly plays the role of shear stress and tensile strength effect. The effect of root reinforcement increases the cohesive strength of soil, decreases soil deformation, prevents the incidence of surface tension cracks, and can avoid slope failure initiated by triggering factors [6][7][8][9][10][11][12][13][14][15][16]. The shear stress is developed in the soil and transferred to the ground as tensile resistance in the roots, which ensures mechanical reinforcement by the roots [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism through which root-reinforced soil is related to concrete reinforcement mainly plays the role of shear stress and tensile strength effect. The effect of root reinforcement increases the cohesive strength of soil, decreases soil deformation, prevents the incidence of surface tension cracks, and can avoid slope failure initiated by triggering factors [6][7][8][9][10][11][12][13][14][15][16]. The shear stress is developed in the soil and transferred to the ground as tensile resistance in the roots, which ensures mechanical reinforcement by the roots [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Slope failure disasters are an universal occurrence on a planet that, like Earth, is tectonically active [7,[15][16][17]. Slope failure along road corridors is one of the critical problems in the mountainous terrain of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…SEEP/W, which employs a finite element method for seepage analyses, and SLOPE/W, which is based on the limit equilibrium method for stability analyses, are GeoStudio software products that many researchers commonly use. In the research by Yeh and Tsai 74 , slopes with uniform soil were put through twodimensional transient seepage analyses using the SEEP/W module to see how changes in the amount of rain in www.nature.com/scientificreports/ 2016, 2050, and 2100 would affect the slope's hydrological state. Afterwards, the results of the seepage analyses were input into the SLOPE/W module to compute the slope safety coefficient.…”
Section: Numerical Analysesmentioning
confidence: 99%
“…Toro-Guerrero et al [7] pointed out that the evaluation of the soil moisture distribution and its variation are crucial for understanding water movement in landslide dams. Yeh and Tsai [8] found that when the soil moisture content increases in a slope, the effective stress and shear strength distinctly decrease. The reduction of effective stress can lead to the collapse of slopes.…”
Section: Introductionmentioning
confidence: 99%